Ethnomathematics-based traditional games as a pedagogical approach to enhance logical-mathematical intelligence - Zayyadi, Moh; Ema Surahmi; Septi Dariyatul Aini; Dayat Hidayat (Universitas Hamzanwadi, 2025)
Research on ethnomathematics-based traditional games that focus on students' mathematical logistic intelligence has not been conducted widely. The purpose of this study was to analyze ethnomathematics-based mathematical games as a learning approach to improve students' logical-mathematical intelligence. Qualitative research was conducted using an exploratory approach. The prospective subjects of this study were 50 students from five Elementary Schools in Pamekasan Regency. Of the 50 students, 10 were selected as research subjects, who were representatives of each traditional game in this study. From the questionnaire given, 10 traditional games that were often played in everyday life were obtained. Data collection techniques were in the form of interviews, observation, documentation, and literature studies as a form of triangulation to obtain data and determine the validity of the data. Data analysis techniques in ethnographic research include descriptions, analyses, and interpretation. The results showed that the integration of traditional games in mathematics learning requires the active role of teachers to link game elements with formal mathematical concepts. Traditional games based on ethnomathematics not only preserve local culture, but also become an effective tool for developing students' logical-mathematical intelligence.